Marketing Mix Perception of Consumer Purchasing Decisions During The Covid 19 Pandemic In Business Gephok Pak Giek Jember Chicken Restaurant - Ajeng Nurdiana Putri; Widodo, Joko; Zulianto, Mukhamad (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Culinary business is also considered as one of the business fields that is easy to do by business actors who have limited capital. The purpose of this study is to determine the significant influence of marketing mix perception on consumer purchasing decisions during the Covid-19 pandemic at Ayam Gephok Pk Giek Jember restaurant. This research is a quantitative research. The population of this study is consumers of Ayam Gephok Pk Giek Jember restaurant. The sample of this study was the Ayam Gephok Pk Giek Jember restaurant. The selection is determined based on probability sampling criteria through accidental sampling. Data collection in this study used questionnaires, observations, interviews, and documentation while the data processing method used editing, scoring and tabulation. The result in this study is the perception of marketing mix as one of the factors that influence consumer purchasing decisions during the Covid-19 pandemic at the Ayam Gepho Pk Giek Jember restaurant. Therefore, there is a significant perception of consumer purchasing decisions during the Covid-19 pandemic at the Ayam Gephok Pk Giek Jember restaurant.